About the base problems of the geomechanics of strong compressed rock and rock masses - Makarov Vladimir (E3S Web of Conferences, 2020)
Some approaches to the simulation of hierarchically-block geomedia are considered. The idea of mesomechanics with allocation of mesovolume of representative scale level is used. It is offered to describe within the frame of geomechanics a rock mass four scale levels considering the conforming hierarchy of structural blocks. On each of these levels the rock mass is presented by non-Euclidian model of a continuous medium with the cracking defects, thus models of different scale levels differ only with values of parametres entering into them.